THE EFFECT OF ICE BREAKING ON MOTIVATING GRADE IV STUDENTS TO LEARN SCIENCE - Mulyadi, Mulyadi; Nurdiansyah, Erwin; Rachman, Sidrah Afriani; Sadaruddin, Sadaruddin (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract: The purpose of this study was to investigate the effect of using one of ice breaking strategies in science learning contexts on students' motivation. This study employed a quantitative approach. The participants involved were 26 students from Class IV A of SD Negeri Daya 1 Makassar City using purposive sampling. Data were collected through observation and questionnaire sheets consisting 30 statements to find students’ motivation levels. Descriptive and inferential statistics were utilized for data analysis. The result indicated that most students’ learning motivation was categorized as good (53.85%) and very good (38.46%) categories after applying yel-yel, one of ice breaking strategies. Therefore, the implementation of ice breaking strategy had a positive impact on enhancing students' motivation to learn science subjects. Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh penggunaan salah satu strategi ice breaking dalam konteks pembelajaran IPA terhadap motivasi siswa. Penelitian ini menggunakan pendekatan kuantitatif. Partisipan yang terlibat adalah 26 siswa Kelas IV A dari SD Negeri Daya 1 Kota Makassar dengan menggunakan purposive sampling. Data dikumpulkan melalui lembar observasi dan angket yang terdiri dari 30 pernyataan untuk mengetahui tingkat motivasi siswa. Statistik deskriptif dan inferensial digunakan untuk analisis data. Hasil penelitian menunjukkan bahwa sebagian besar motivasi belajar siswa berada pada kategori baik (53,85%) dan sangat baik (38,46%) setelah diterapkannya strategi yel-yel yang merupakan salah satu strategi ice breaking. Oleh karena itu, penerapan strategi icebreaking memberikan dampak positif terhadap peningkatan motivasi belajar siswa pada mata pelajaran IPA.